2018
DOI: 10.1111/jfbc.12534
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ethylene and ethephon treatments on the peel color and carotenoids of Gannan Newhall navel orange during postharvest storage

Abstract: Gannan Newhall navel orange was treated by ethylene and ethephon separately. The color of Gannan Newhall navel orange peel was influenced significantly by ethylene and ethephon treatments. During postharvest storage, the ratio of chlorophylls and carotenoids in the peel reduced which led the peel color changing from green to yellow when treated by ethephon and to orange‐red when treated by ethylene. Results of the CIELAB chroma system evaluation were consistent with sensory evaluation. Ethylene and ethephon tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…With the 'Navelina' oranges, degreening treatment enhanced the colour from pale orange tones at harvest to intense orange tones (Figure 2 and 3). Orange colour development of the citrus peel as result of the degreening treatment has been associated with the accumulation of carotenoid pigments, such as zeaxanthin and mainly β-cryptoxanthin and β-citraurin (Hu et al, 2018;Sumiashi et al, 2018). It is noteworthy that temperature itself had an effect on the rind colour of the studied three mandarins as the control fruit showed enhanced colour compared to the fruit at harvest (Figure 3).…”
Section: Effect Of Ethylene Degreening On Physico-chemical Parameters Is Cultivardependentmentioning
confidence: 99%
See 1 more Smart Citation
“…With the 'Navelina' oranges, degreening treatment enhanced the colour from pale orange tones at harvest to intense orange tones (Figure 2 and 3). Orange colour development of the citrus peel as result of the degreening treatment has been associated with the accumulation of carotenoid pigments, such as zeaxanthin and mainly β-cryptoxanthin and β-citraurin (Hu et al, 2018;Sumiashi et al, 2018). It is noteworthy that temperature itself had an effect on the rind colour of the studied three mandarins as the control fruit showed enhanced colour compared to the fruit at harvest (Figure 3).…”
Section: Effect Of Ethylene Degreening On Physico-chemical Parameters Is Cultivardependentmentioning
confidence: 99%
“…In fact, in European Union markets, the proportion of the fruit surface with a minimum colouration is one of the maturity indexes used to define fruit quality (Lado et al, 2018). Thus a common practice to enhance the skin colour development of early citrus cultivars is to apply the ethylene degreening treatment (Machado et al, 2015;Da Costa et al, 2017;Hu et al, 2018). Citrus fruit are classified as non-climateric according to their respiration and ethylene production patterns (Kader, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Which is evident from the various past research findings in climacteric fruits [44]. Although relatively few studies have been carried out on non-climatic fruits, recent studies have shown that ethylene also has an important role to play in the coloring and maturation of grape berries [45,46]. However, the application of ethephon observed dual effect on grape fruit ripening.…”
Section: Influence Of Ethylene On the Grape Fruit Physiological And Mmentioning
confidence: 97%
“…Thus, the degreening treatment developed Agronomy 2022, 12, 270 2 of 12 in controlled chambers is considered as one of the postharvest strategies used to promote the optimal harvest time of lemon fruits independently of environmental conditions. In organic production, temperature, relative humidity, and carbon dioxide concentrations are controlled during the postharvest storage of lemon fruits until they change their skin colour from green to favourable yellow, since nowadays the exogenous application of ethylene is banned [7].…”
Section: Introductionmentioning
confidence: 99%